Natural regeneration in an area of shallow cut Pinus taeda L. - Secco, Rubia Tatiana (2019)
The present study aimed the ﬂoristic analysis of natural regeneration in Pinus taeda L. shallow cut area approximately two years after suppression of a planting of about fifteen years. The study area is located in the city of Campo Largo – PR state, which original forest typology belongs to the Araucaria Rainforest, a total of 5.5 hectares. For the sampling of the natural regeneration of the area, ten plots of 10m x 10m each were installed, and, within each of them, five subplots totaling 5m², of which were collected all individuals with arboreal characteristics, sample adequacy was achieved. It was sampled 406 individuals belonging to 64 botanical species. The family Asteraceae showed the highest number of copies, followed by Solanaceae and Primulaceae. The ecological diversity index of Shannon, and the equability index of Pielou presented values of 3.42 and 0.82 respectively. The number of individuals in pinus regeneration in the study area was 23 copies, with a high value when compared to other species. However, it can be concluded that the number of native individuals, as well as the species richness of the natural regeneration, showed no impairment due to previous settlement with exotic species.